Regulate DPR’s Committees: Making Indonesian Presidential System More Representative - Zulkarnain Ridlwan; Zainal Arifin Mochtar (Universitas Lampung, 2019)
The evaluation of the DPR's oversight function always considered not to represent the will of critical supervision of the people in almost every DPR's performance satisfaction survey. The DPR Committees institutionally the main actor of supervision, but has not been effective. 11 DPR committees compared to 113 work partners suspected to be one of the causes. Committees formed by DPR and can be adjusted according to needs. Based on a comparative approach on regulations in the US Congress and the British Parliament, it is recommended to narrow the oversight work by increasing the number of DPR committees to balance a large number of partners. The division of supervision work into more committees makes the scope of work narrow so that supervision is more focused. Changes in the arrangement of the number of committees in Law 17/2014 and the DPR 2014 Rules of Conduct need to be done by stating the maximum number of five working partners for each committee. The creativity of the committee to form sub-committees in accordance with needs must also be confirmed in the 2014 DPR Rules of Conduct. Such regulation is expected to make the performance of checks and balances between the DPR and the Government be better assessed by the public as a unitary presidential government system, namely a presidential system that better represents the will of the people's supervision.